DEVELOPMENT AREAS IN THE ARCTIC REGION FORMATION OF A NEW INSTITUTIONAL SPACE - M. Dudin; N. Lyasnikov (Модернизация, инновация, развитие, 2016)
Retracted articleIn this article we presented and disclosed some abstracts related to the problems of development of the Arctic and subarctic areas, which according to various expert estimates contain from 15 to 25% of the world reserves of primary energy resources, as well as the study examines the current situation and prospects of the Russian Federation the process of development of the Arctic territories.The purpose of this article is to study Russia's priorities at the national and regional levels related to the extraction of minerals that can be used to enhance the competitiveness of Russia on the world level and to ensure national energy security. Also, a study of this article is aimed at addressing issues related to the development of recommendations for the development of the global system of economic and energy security in the context of exploitation of prospective deposits in the Arctic region.Methodology. The methodological basis of this article are comparative and economic-statistical methods of analysis.Results: In this article were subsequently solved the problem, to achieve this goal, in particular: examined the general trends of energy development of civilization, considered the legal issues concerning the status of the Arctic and the Arctic regions, the basic global trends of world energy development and justifi ed system for ensuring global energy security.Conclusions. There were obtained the following basic conclusions: First, the Arctic and the Arctic area are world heritage, so the development of deposits on them should be in the interest of the world community on a non-discriminatory basis; secondly, energy future civilization will be based on the harmonious combination of traditional and renewable energy sources, which determines the need to rationalize the consumption of energy resources in the present; Third, environmental issues prospects of development of the Arctic and subarctic areas suffi ciently sharp and discussion, therefore, should be used in aggressive technology of extraction of primary energy resources of the Arctic fi elds. It was found that theimprovement of conditions for the dissemination and implementation of technological innovation in reducing or optimizing the geopolitical, military, economic, environmental, cultural risks in the Arctic region involve: support for research centers, producing technological innovations in the fi eld of exploration and development of the Arctic shelf, and broadcasting their respective corporations; the development of infrastructure to reduce the institutional, economic and technological backwardness of the State leaders and to achieve the highest standards of safety and performance standards.